Comparative Analysis Retrofit and Ktor Client Performance in Various Internet Speeds Internet on MSMEs Cashier Application - Kholik, Muhamad Akbar Abdul; Pratomo, Dinar Nugroho (Jurnal Teknik Informatika (Jutif), 2025)
MSMEs (Micro, Small, and Medium Enterprises) in Indonesia face uneven network infrastructure, with more than 20% of smartphone users having download speeds below 10 Mbps. This condition hampers the efficiency of data processing between client and server, while MSMEs need innovations such as digitization of bookkeeping to increase competitiveness. The selection of HTTP networking libraries such as Retrofit and Ktor Client is very important, because both play a role in the process of sending and receiving data from the server. This research aims to analyze the performance of both libraries in the Lulu POS application to determine the most optimal library in supporting MSME operations in various network conditions. The test is conducted in two scenarios: the first scenario uses text data and the second scenario uses text and image data. Each scenario has several test cases that will be tested at six different internet speeds. The results show that Retrofit excels in response time for text data with a performance improvement of 18.85% and network usage of 21.33%. Ktor Client is superior in scenarios involving text and image data, with a response time advantage of 7.20% and network usage of 0.08%. On the other hand, Retrofit is more efficient in memory usage in both scenarios, with an advantage of 16.49% in text data and 4.70% in text and image data. In conclusion, Retrofit is more stable for applications focusing on text data such as Lulu POS, while Ktor Client is more suitable for applications that manage images. These results make MSMEs get cashier applications with optimal libraries for various network conditions, so that operations are smoother and data management efficiency increases.